2003
DOI: 10.1111/j.1550-7408.2003.tb00148.x
|View full text |Cite
|
Sign up to set email alerts
|

Interstitial Ciliates: Benthic Microaerophiles or Planktonic Anaerobes?

Abstract: We observed marine benthic interstitial ciliates Geleia sp. and Tracheloraphis sp. inhabiting the water column of a chemically stratified salt pond. This habitat is uncharacteristic for interstitial ciliates, yet they displayed active and abundant planktonic populations (up to 800 and 250 cells/liter, respectively) and a well-defined pattern of vertical distribution. Completely absent from the oxygenated epilimnion, they first appeared at the oxic/anoxic interface and were present throughout the anoxic hypolim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 11 publications
0
10
0
Order By: Relevance
“…Euglenid flagellates matching most closely to Diplonema and ciliates of the Litostomatea increased in relative abundance in the OMZ, particularly in the larger size fraction. Diverse euglenids and ciliates are common inhabitants of anaerobic and microaerophilic marine waters (Bernard and Fenchel, 1996 ; Hayward et al, 2003 ; Orsi et al, 2011 , Table 2 ). Clone-based molecular studies of OMZs have identified a new class of euglenids (Symbiontida) that are closely related to diplonemids, common in low oxygen waters, and appear to host sulfide-oxidizing, nitrate-reducing epibiotic bacteria (Edgcomb et al, 2010 ; Orsi et al, 2011 , 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…Euglenid flagellates matching most closely to Diplonema and ciliates of the Litostomatea increased in relative abundance in the OMZ, particularly in the larger size fraction. Diverse euglenids and ciliates are common inhabitants of anaerobic and microaerophilic marine waters (Bernard and Fenchel, 1996 ; Hayward et al, 2003 ; Orsi et al, 2011 , Table 2 ). Clone-based molecular studies of OMZs have identified a new class of euglenids (Symbiontida) that are closely related to diplonemids, common in low oxygen waters, and appear to host sulfide-oxidizing, nitrate-reducing epibiotic bacteria (Edgcomb et al, 2010 ; Orsi et al, 2011 , 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…Among these are many bacterivorous ciliates, such as Tiarina and Pleuronema; diatom feeders, including Chlamydodon; herbivores that feed on flagellates and diatoms, like Condylostoma; carnivores, such as Trachelocera and Tracheloraphis; and also histophagous forms, such as Coleps and Prorodon, all of which were detected in the oxic surface sediments in our experiment (Supplement 1). Some of these species can live at the oxic−anoxic interface, and cope with alternating oxic and anoxic conditions (Hayward et al 2003). Taxa such as Coleps, Pleuronema and most karyorelicteans (Carey 1992) can tolerate the anoxic sediments for short periods of time.…”
Section: Discussionmentioning
confidence: 99%
“…However, some of the microaerophilic ciliates (those that tolerate low oxygen levels) can move vertically from sediment to the water column, demonstrating the ability to transport organic matter upwards [14,20,31]. In addition to protozooplankton, some copepods and Daphnia have been reported to migrate downwards in the water column, descending during daylight into low oxygen levels to feed or to escape predation and ascending at night hours [1,3,7,39,44].…”
Section: Discussionmentioning
confidence: 99%